Impact of periprocedural pulmonary hypertension on outcomes after TAVR: novel risk stratification from the OCEAN-TAVI Registry. (3rd October 2022) - Miyamoto, J; Ohno, Y; Ikari, Y; Tada, N; Naganuma, T; Yamawaki, M; Yamanaka, F; Shirai, S; Mizutani, K; Tabata, M; Ueno, H; Takagi, K; et al.
Abstract: Aim: There are limited data on prognostic impact of periprocedural pulmonary hypertension (PH) after transcatheter aortic valve replacement (TAVR). The aim of this study was to investigate the prognostic impact of normalized, new-onset, and residual PH after TAVR. Methods and results: OCEAN-TAVI registry is an ongoing, multicenter Japanese registry which includes 2588 patients who underwent TAVR. Patients were classified into 4 groups according to periprocedural systolic pulmonary artery pressure (sPAP) by echocardiography: pre-no PH/post-no PH (no PH) group, pre-PH/post-no PH (normalized PH) group, pre-no PH/post-PH (new-onset PH) group, and pre-PH/post-PH (residual PH) group. PH was defined as sPAP>36mmHg. Primary endpoint was all-cause mortality at 2 years. Logistic regression analysis was used to identify the clinical predictors of residual and new-onset PH. In total, 1872 patients were divided into 4 groups: 1027 patients (54.9%) in the no PH, 257 patients (13.7%) in the normalized PH, 280 patients (15.0%) in the new-onset PH, and 308 patients (16.5%) in the residual PH group, respectively. There was a significant difference in all-cause mortality among the 4 groups at 2 years (11.0%, 12.8%, 18.6%, and 24.7%, respectively; P<0.01). Among 565 patients who had pre-procedural PH, 257 patients (45.5%) experienced normalization of PH with mortality comparable with no PH group. In multivariable logistic regression analysis, predictors of residual PH after TAVR were atrial fibrillation and baseline tricuspid regurgitation>moderate, whereas prosthesis-patient mismatch (PPM) was a predictor of new-onset PH. Conclusions: Risk stratification based on improvement in PH or new-onset/residual PH after TAVR can identify patients at increased mortality after TAVR. PPM was identified as a novel predictor of new-onset PH. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The OCEAN-TAVI registry is supported by Edwards Lifesciences, Medtronic Japan, Boston Scientific, Abbott Medical, and Daiichi-Sankyo company.